Add-on inhaled budesonide in the treatment of hospitalised patients with COVID-19: a randomised clinical trial. Issue 3 (10th March 2022) - Agustí, Alvar; De Stefano, Gaston; Levi, Alberto; Muñoz, Xavier; Romero-Mesones, Christian; Sibila, Oriol; Lopez-Giraldo, Alejandra; Plaza Moral, Vicente; Curto, Elena; Echazarreta, Andrés L.; Márquez, Silvana E.; Pascual-Guàrdia, Sergi; et al.
SARS-CoV-2 vaccines have been extremely effective in reducing the incidence of severe coronavirus disease 2019 (COVID-19) [1, 2], but effective and safe treatments for acute infection are still limited [3, 4]. An uncontrolled pulmonary inflammatory response to SARS-CoV-2 is considered a key pathogenic mechanism of COVID-19 progression [5], so systemic dexamethasone is recommended in severe cases [4, 6]. On the other hand, in very mild patients at home, inhaled corticosteroids (ICS) may prevent disease progression [7–10]. Whether ICS can also prevent disease progression in patients hospitalised because of COVID-19 has not been explored previously. Accordingly, we designed an investigator-initiated, open-label, randomised clinical trial (RCT) to explore the efficacy of adding inhaled budesonide to usual care to prevent disease progression in patients hospitalised because of COVID-19 pneumonia. We also carefully monitored the safety of this intervention since there are concerns about the use of systemic corticosteroids in other viral (influenza) lung infections [11]. The addition of inhaled budesonide to usual care is safe and may reduce the risk of disease progression in patients hospitalised because of COVID-19 pneumonia https://bit.ly/3tEQo3p